Synergy between supported ionic liquid-like phases and immobilized palladium N-heterocyclic carbene–phosphine complexes for the Negishi reaction under flow conditions - Peris, Edgar; Porcar, Raúl; Macia, María; Alcázar, Jesús; García-Verdugo, Eduardo; Luis, Santiago V. (Beilstein Journal of Organic Chemistry, 2020)
The combination of supported ionic liquids and immobilized NHC–Pd–RuPhos led to active and more stable systems for the Negishi reaction under continuous flow conditions than those solely based on NHC–Pd–RuPhos. The fine tuning of the NHC–Pd catalyst and the SILLPs is a key factor for the optimization of the release and catch mechanism leading to a catalytic system easily recoverable and reusable for a large number of catalytic cycles enhancing the long-term catalytic performance.
Keywords: immobilized catalyst; Negishi cross-coupling; NHC complex; palladium; supported ionic liquid